White-lipped peccary home-range size in the maya forest of Guatemala and México - Moreira-Ramírez, José Fernando; Reyna-Hurtado, Rafael; Hidalgo-Mihart, Mircea; Naranjo, Eduardo J.; Ribeiro, Milton C. [UNESP]; García-Anleu, Rony; McNab, Roan; Radachowsky, Jeremy; Mérida, Melvin; Briceño-Méndez, Marcos; Ponce-Santizo, Gabriela (Springer Nature, 2019)
The white-lipped peccary (Tayassu pecari, Link 1795) is a social ungulate that lives in large groups and performs large movements across tropical forest searching for food and water. White-lipped peccaries are an important food source among rural communities. Nevertheless, excessive hunting has caused the extirpation of this species from several areas in the Neotropics where it was previously common. Throughout its range it is considered vulnerable according to the IUCN Red List of Threatened Species, but the Mesoamerican population has decreased in the last 20 years at alarming rates. Using satellite GPS collars, kernel density estimate (KDE), minimum convex polygon (MCP), and the autocorrelated kernel density estimation (AKDE), we estimated the spatial requirements of four white-lipped peccary groups in three sites with different levels of hunting pressure in the Maya Forest of Guatemala and México. Our results showed that the home range estimated in non-hunted sites were smaller than in hunted sites. The 95% KDE home range for non-hunted areas ranged between 40 and 99 km2, substantially smaller than that of the hunted area at 140 km2. Similarly, the 95% AKDE area estimates for non-hunted sites ranged from 62 to 156 km2, while for the hunted site, the 95% AKDE estimate was 312 km2. In non-hunted sites, dry season home ranges were constrained to the close vicinity of water ponds, whereas during the rainy season white-lipped peccary groups were more mobile. In contrast, the home range was larger in the hunted site during the dry season compared with rainy season. Our results suggest that hunting pressure in the Maya Forest is probably affecting the behavior and ecology of the peccary group, causing them to move through larger areas with lower group size in hunted areas compared to non-hunted areas. We hope that these results encourage more studies focused on estimating white-lipped peccary home-range size in areas with hunting pressure and human activities.
Keywords: Autocorrelated kernel density estimation; Fixed kernel; GPS telemetry; Home range; Hunting; Minimum convex polygon; Spatial ecology; Tayassu pecari; White-lipped peccary